Uwagi na temat ‘Inaugural Speech’ Joe Bidena jako aktu retorycznego w świetle klasycznej teorii retoryki - Tuszyńska, Krystyna (Scripta Neophilologica Posnaniensia, 2021)
The article performs an analysis of 46th USA President’s inaugural speech in the spirit of Neo-Aristotelian concepts. The article also contains an analysis of inaugural speech genre, matching Joe Biden’s case as a hybrid, and analyses elocutio and the way the speaker claims the space of communication. The article also refers to Aristotle’s concept of ethos.